Shaming et mises en scène de pratiques journalistiques « déloyales » dans les documentaires télévisuels d’investigation. - Gilles Labarthe (Communication)
How does a team of television investigative journalists behave when it is refused access to sources? How and when does it decide to resort to underhanded practices? Based on an exploratory socio-ethnographic observation of a French team, the author examines situations revealing the discrepancies between the justifications proffered by the journalists and their actions. He details the underhanded practices used — including hidden cameras — and suggests that the notion of “shaming” is one of the keys to understanding the constraints such journalists face.